The central mechanotransducer in osteoporosis pathogenesis and therapy - Liu, Chaoyue; Yang, Jihao; Dong, Zengsheng; Zhao, Shuqing; Tian, Zeng-Hui; Li, Ying-Ying; Hao, Yan-Ke; Wang, Mingliang (Frontiers in Endocrinology, 2025)
This review identifies the mechanosensitive ion channel Piezo1 as the central regulator of bone homeostasis. Piezo1 senses mechanical loads in osteocytes, osteoblasts, and bone marrow mesenchymal stem cells (BMSCs), converting them into Ca2+-dependent signals that activate key pathways, including CaMKII, YAP/TAZ, Wnt/β-catenin, and ERK. These cascades collectively promote osteoblast differentiation and suppress osteoclastogenesis via OPG/RANKL modulation. Age-related Piezo1 decline impairs bone mechanoresponsiveness, driving both senile and disuse osteoporosis. Piezo1 also integrates bone metabolism with vascular–immune interactions (e.g., promoting VEGFA release from bone marrow macrophages via the CaN/NFAT/HIF-1α pathway) and the gut–bone axis (e.g., intestinal Piezo1 deletion relieves osteoblast proliferation inhibition by reducing serotonin levels). Therapeutically, Piezo1 agonists restore bone mass in osteoporosis models by reactivating mechanotransduction, while physical interventions achieve similar effects. Outstanding challenges include optimizing mechanical parameters (e.g., vibration frequency, ultrasound intensity) for individualized therapy, disentangling pathway crosstalk under aging and inflammation, and developing bone-targeted delivery systems for Piezo1 modulators. Overall, Piezo1 emerges as a pivotal therapeutic target for osteoporosis.